PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN - Pinesty, Tri; Retnaningdiah, Dian (Kajian Ekonomi dan Bisnis, 2025)
Competition in the pharmaceutical industry is getting more intense along with the economicdevelopments and increasing public awareness of the importance of health. Thus, companies needto manage financial policies optimally to increase company value. Research objective: to examinethe impact of debt policy, dividend policy, and profitability on the value of pharmaceuticalsubsector companies listed on the Indonesia Stock Exchange (BEI) between 2021 and 2023. Thestudy's dependent variable is firm valuation, whereas the independent variables are profitability,dividend policy, and debt policy. Research method: This study employed a quantitative approachwith secondary data in the form of annual financial reports obtained through a purposivesampling method from four pharmaceutical companies for three years. Research results: Itdemonstrates that while debt policy has no discernible impact on firm value, profitability anddividend policy do have a positive and considerable impact. The study's independent variableshave a great ability to explain fluctuations in company value, as seen by the coefficient ofdetermination (Adjusted R2) of 87.6%. Conclusion: These findings support the Signaling Theory,where profitability and optimal capital structure provide positive signals to investors. Theseresultsare expected to be a consideration for company management and investors in making strategicdecisions.